Germline biallelic BRCA2 pathogenic variants and medulloblastoma: an international cohort study - Kastellan, Svenja; Kalb, Reinhard; Sajjad, Bia; McReynolds, Lisa J.; Giri, Neelam; Samuel, David; Milde, Till; Elbracht, Miriam; Holzhauer, Susanne; Niewisch, Marena R.; Kratz, Christian P. (Journal of hematology & oncology, 2024)
Constitutional heterozygous pathogenic variants in genes coding for some components of the Fanconi anemia-BRCA signaling pathway, which repairs DNA interstrand crosslinks, represent risk factors for common cancers, including breast, ovarian, pancreatic and prostate cancer. A high cancer risk is also a main clinical feature in patients with Fanconi anemia (FA), a rare condition characterized by bone marrow failure, endocrine and physical abnormalities. The mainly recessive condition is caused by germline pathogenic variants in one of 21 FA-BRCA pathway genes. Among patients with FA, the highest cancer risks are observed in patients with biallelic pathogenic variants in BRCA2 or PALB2. These patients develop a range of embryonal tumors and leukemia during the first decade of life, however, little is known about specific clinical, genetic and pathologic features or toxicities. Here, we present genetic, clinical, pathological and treatment characteristics observed in an international cohort of eight patients with FA due to biallelic BRCA2 pathogenic variants and medulloblastoma (MB), an embryonal tumor of the cerebellum. Median age at MB diagnosis was 32.5 months (range 7-58 months). All patients with available data had sonic hedgehog-MB. Six patients received chemotherapy and one patient also received proton radiation treatment. No life-threatening toxicities were documented. Prognosis was poor and all patients died shortly after MB diagnosis (median survival time 4.5 months, range 0-21 months) due to MB or other neoplasms. In conclusion, MB in patients with biallelic BRCA2 pathogenic variants is a lethal disease. Future experimental treatments are necessary to help these patients.